CONCEPT-ORIENTED READING INSTRUCTION (CORI) FOR BETTER READING COMPREHENSION - Restu Damai Laia (Institut Pendidikan Tapanuli Selatan, 2020)
This research aimed at testing the effect of Concept-Oriented Reading Instruction (CORI) on students’ reading comprehension. This research was a quasi-experimental research. It was conducted at Semester IV of English Language Education Study Program of STKIP Nias Selatan. The samples were chosen by using cluster random sampling technique. The samples of this research were 2A as experimental class (23 students) and 2B as control class (23 students). Reading comprehension test was used to collect the data of the research. The data were analyzed by using Chi-square test for normality testing, variance test for homogeneity testing, and t-test for hypotheses testing. The result of data analysis showed that Concept-Oriented Reading Instruction (CORI) produced better reading comprehension of students than Contextual Teaching and Learning. Based on the finding, it is concluded that Concept-Oriented Reading Instruction is an effective instructional strategy for students’ reading comprehension compared to Contextual Teaching and Learning.